General combining ability and heterosis regarding the phytochemical properties in strawberry (Fragaria × ananassa) hybrids. (9th December 2016) - Kaczmarska, Elżbieta; Gawroński, Jacek; Jabłońska‐Ryś, Ewa; Zalewska‐Korona, Marta; Radzki, Wojciech; Sławińska, Aneta
Abstract: Strawberries are a common and important fruit in human diet because of their high content of essential nutrients and beneficial phytochemicals, which have relevant biological activity in human health. In this study, six cultivars and 15 selected F1 hybrids between S4 inbred lines and tester (cv. 'Dukat') were evaluated in a field trial over a period of two consecutive years. The amounts of total anthocyanin, phenolics and vitamin C in fruits and antiradical activity were analysed. General combining ability (GCA) and mid‐parent heterosis were also determined for those characteristics. Among all the genotypes tested, the inbred lines of 'Senga Sengana' 17 showed the highest breeding value based on GCA for all studied traits. Estimated heterosis varied among genotypes tested. The highest heterosis in terms of vitamin C occurred in the offspring of clone 1387 18‐15 × 'Dukat', but with regard to phenols and antiradical activity in hybrid 'Teresa' 18‐15 with cv. 'Dukat'. This study revealed that the differentiation in chemical composition of strawberry fruits between genotypes is clearly dependent on individual genotype combinations and demonstrated the presence of heterosis in phytochemical contents in some specific genotypic combinations.